2013
DOI: 10.1016/j.parkreldis.2012.07.002
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo microglia activation in very early dementia with Lewy bodies, comparison with Parkinson's disease

Abstract: [(11)C]-PK11195 Positron Emission Tomography imaging revealed neuroinflammation in dementia with Lewy bodies and Parkinson's disease, mirroring, even at a single subject level, the common and the different topographical distribution of neuropathological changes, yet in the earliest stages of the disease process. Focusing on those events that characterize parkinsonisms and Parkinson's disease may be the key to further advancing the understanding of pathogenesis and to taking these mechanisms forward as a means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(154 citation statements)
references
References 34 publications
13
140
0
1
Order By: Relevance
“…Alternatively, microglial activation could switch on and off depending on the nature of the insult-it is known that after stroke microglial activation eventually subsides. Recent study in a small number of subjects have demonstrated that microglial activation is also elevated in subjects with Lewy body dementia (Iannaccone et al, 2012) A previous study from our group of non-demented PD subjects reported the presence of raised microglial activity in subcortical regions, including striatum, pallidum, thalamus, and pons along with cortical regions (Gerhard et al, 2006). We have replicated those findings in this new study with ROI analysis.…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, microglial activation could switch on and off depending on the nature of the insult-it is known that after stroke microglial activation eventually subsides. Recent study in a small number of subjects have demonstrated that microglial activation is also elevated in subjects with Lewy body dementia (Iannaccone et al, 2012) A previous study from our group of non-demented PD subjects reported the presence of raised microglial activity in subcortical regions, including striatum, pallidum, thalamus, and pons along with cortical regions (Gerhard et al, 2006). We have replicated those findings in this new study with ROI analysis.…”
Section: Discussionsupporting
confidence: 84%
“…11 C]PK11195 binding was also increased in the anterior and posterior cingulate, striatum, frontal, temporal, parietal, and occipital cortical regions in PDD patients (Edison et al, 2013) and in the substantia nigra, putamen, and several associative cortices of DLB patients (Iannaccone et al, 2013).…”
Section: Neuroinflammationmentioning
confidence: 93%
“…Okello et al [42] showed increased binding of 11 C-PK11195 in the frontal cortex in a small group of PiB-positive versus PiB-negative MCI patients. Neuroinflammation was also reported in DLB patients compared with controls [43]. Conversely, a more recent study comparing patients with probable AD, MCI patients and healthy controls did not demonstrate significant differences in uptake between the groups [44].…”
Section: Dementiasmentioning
confidence: 93%